2019
DOI: 10.3390/medicina55050168
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety–Depression of Dialysis Patients and Their Caregivers

Abstract: Background and Objectives: Anxiety–depression of patients undergoing hemodialysis has a strong relation with the levels of anxiety–depression of their caregivers. The aim of this study was to evaluate anxiety–depression of dialysis patients and their caregivers. Materials and Methods: In this cross-sectional study, 414 pairs of patients and caregivers from 24 hemodialysis centers of Greece completed the Hospital Anxiety and Depression Scale (HADS). The statistical analysis of the data was performed through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 31 publications
1
40
0
2
Order By: Relevance
“…Moreover, 70.5% of the participants reported low levels of depression, while 17.1% and 12.3% showed moderate and high levels of depression, respectively. 7 In fact, renal failure impacts the hemodialysis patients' emotional status as a result of dietary and fluid restrictions, pain, and fatigue. 36 Therefore, it leads to psychological issues, such as depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, 70.5% of the participants reported low levels of depression, while 17.1% and 12.3% showed moderate and high levels of depression, respectively. 7 In fact, renal failure impacts the hemodialysis patients' emotional status as a result of dietary and fluid restrictions, pain, and fatigue. 36 Therefore, it leads to psychological issues, such as depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The Personal Resources Questionnaire-85 (PRQ-85) Part II (https://www.ncbi.nlm.nih.gov/pubmed/3306610) 28 was used to measure the patients' perceived social support. PRQ-85 Part II contained 25 items responded via a sevenpoint Likert-type scale with end points of strongly disagree (1) and strongly agree (7). Thus, the total score of the questionnaire could range from 25 to 175, with higher scores representing higher levels of perceived social support.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety and depression are common psychiatric disorders among patients undergoing hemodialysis (HD). Several factors seem to trigger anxiety and depression in hemodialysis patients such as co-morbidities, frequent hospitalizations, chronic pain, sleep disturbances, chronic inflammation, increased fatigue, uremia, failure of family support restrictions in daily life, non-compliance to therapeutic regimen including restrictions in diet and fluids, and dependency upon treatment and health professionals [1].…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that there was a significant correlation between anxiety and depression levels of the hemodialysis patients and caregivers 2012;Sajadi et al, 2017). It is necessary to individually evaluate the dialysis patients and professional caregivers administering treatment to these patients and to apply special interventions in order to reduce anxiety and depression levels among them (Gerogianni et al, 2019). Assistant health personnel working in the dialysis unit should pay attention to personal hygiene and should be ensured to work with protective equipment (mask, gloves, protective gown, disinfectant).…”
Section: Introductionmentioning
confidence: 99%